Effects of low radioactivity of the Yemeni’s Catha edulis (Khat) and tobacco plants - AL-Jalali, Muhammad (International Journal of Physical Research, 2014)
The present work aims to shed light on the relationship between the cause of cancer and low radioactivity distribution of Catha edulis (Khat) and tobacco grown in Yemen, whereas they have a remarkable relationship with human health, due chewing of Catha edulis and smoking tobacco simultaneously. The complicated behavior of smoking tobacco and chewing Catha edulis at the same time could be responsible for different kinds of cancer diseases. Wavelength Dispersive X-ray Fluorescence (WDXRF) spectrometer was used to specify the chemical composition of Catha edulis and tobacco plants. In addition, radioactive detectors reveal the distribution of the radioactivity of Catha edulis and Tobacco plants is higher than the natural radioactivity distribution, because of the presence of the heavy minerals and different radioisotopes in Catha edulis and Tobacco plants. Keywords: Low Radioactivity, Catha Edulis, Tobacco, WDXRF, Oral and Lung Cancers.